Adaptive time division power dispatch based on numerical characteristics of net loads. (15th August 2020) - Hu, Shu-bo; Gao, Zheng-nan; He, Hai; Cao, Wen-ping; Zhao, Yu-ting; Zhou, Wei; Gu, Hong; Sun, Hui
Abstract: Energy sustainable development is of strategic importance across the world. This is especially the case in China as it is the world's largest energy consumer. However, renewable energies such as wind and solar energy are characterized with high intermittence and fluctuation. As the penetration of renewable power in the energy system increases, it is getting more challenging in power dispatch. In this paper, an adaptive time division power dispatch strategy based on numerical characteristics of net loads is proposed. In this strategy, a dispatch time division method is introduced in detail to divide the dispatching time according to the numerical characteristics of net loads. The sample entropy theory is utilized to calculate the complexity of the net loads, depending on which a specific thermal generating mode is provided. The experiment simulation is developed on an actual provincial power system in the northeast of China. The test results have confirmed that in the adaptive time division power dispatch strategy, the ramping power of thermal generators are decreased, the continuous and steady operation time of thermal generators are improved. As a result, this new strategy, can lead to improved energy efficiency of power systems as well as significant environmental benefits. Highlights: A dispatch time division method is proposed according to the numerical feature of the net loads. A complexity calculation method of each net load subsequence based on SampEn is introduced. The specific net load numerical characteristic fitted thermal operation mode is introduced. An adaptive time division power dispatch strategy based on the complexity of net loads is provided. An actual provincial power grid in the northeast of China is developed to illustrate the effectiveness and practicability.